(Re) Konstruksi setting riset untuk suatu studi etnografi praktik akuntansi di sebuah perusahaan swasta nasional - eddy R. Rasyid (Jurnal Akuntansi dan Auditing Indonesia, 2001)
In the recent accounting case study literature, a story of the construction of the research field is missing. It makes the readers unable to gain an understanding of the local nuances of the field where the research takes place at the time of the presence of the researches. As such, the readers have been made unable to develop better their own understanding of the research reports being presented. The authors of this article maintain that if we believe that a researcher is not sparated from her/his research, the story of access construction is needed to be accounted as an integral part of the tales of the field. This article provides process has been acauireda careful attention by researchers who are considering and planning to undertake such field research.